Balancing Competences? Proportionality as an Instrument to Regulate the Exercise of Competences after the PSPP Judgment of the Bundesverfassungsgericht. (16th June 2021) - Petersen, Niels; Chatziathanasiou, Konstantin
Abstract : Analysis of proportionality in the context of Article 5 TEU after the PSPP judgment – Bundesverfassungsgericht challenging Court of Justice to control European Central Bank's motives – Doctrinal tradition of 'smoking out' illicit motives through proportionality – Article 5(4) TEU: proportionality of exercise of competences, primarily safeguarding member states' autonomy – Court of Justice case law on proportionality: deferential standard of review towards measures of EU institutions – Bundesverfassungsgericht case law on federal competences and municipal autonomy: less deferential but still respectful standard of review – PSPP inconsistent with case law and with Article 5 TEU – Balancing-stage of proportionality unsuitable for motive control